Crossing borders : political essays - Crick, Bernard, 1929-2008 (Bloomsbury academic collections. History and politics in the 20th century : Europe., 2016)
"Bernard Crick's mastery of the political essay is matched by few, if any, modern political writers. This new collection demonstrates the wide range of his writing with characteristically bold, argumentative and witty pieces on British identity, on the Northern Irish peace process, on New Labour, on Shaw, Berlin, Laski and Arendt, and on the present state of political writing. It will enlighten, provoke and amuse readers keen to engage with political ideas and arguments current at the turn of the millennium."--Bloomsbury Publishing